Effect of Incisional Negative Pressure Wound Therapy vs Standard Wound Dressing on the Development of Surgical Site Infection after Spinal Surgery: A Prospective Observational Study. Issue 5 (20th May 2021) - Mueller, Kyle B; D'Antuono, Matthew; Patel, Nirali; Pivazyan, Gnel; Aulisi, Edward F; Evans, Karen K; Nair, M Nathan
Abstract: BACKGROUND: Use of a closed-incisional negative pressure therapy (ci-NPT) dressing is an emerging strategy to reduce surgical site infections (SSIs) in spine surgery that lacks robust data. OBJECTIVE: To determine the impact of a ci-NPT, as compared with a standard dressing, on the development of SSIs after spine surgery. METHODS: This was a prospective observational study over a 2-yr period. Indications for surgery included degenerative disease, deformity, malignancy, and trauma. Exclusion criteria included anterior and lateral approaches to the spine, intraoperative durotomy, or use of minimally invasive techniques. SSIs up to 60 d following surgery were recorded. RESULTS: A total of 274 patients were included. SSI rate was significantly lower with ci-NPT dressing (n = 118) as compared with the standard dressing (n = 156) (3.4 vs 10.9%, P = .02). There was no statistical difference in infection rate for decompression alone procedures (4.2 vs 9.1%, P = .63), but there was a statistically significant reduction with the use of a negative-pressure dressing in cases that required instrumentation (3.2 vs 11.4%, P = .03). Patients at higher risk (instrumentation, deformity, and malignancy) had less SSIs with the use of ci-NPT, although this did not reach statistical significance. There were no complications in either group. CONCLUSION: SSI rates were significantly reduced with a ci-NPT dressing vs a standard dressing in patients who underwent spinal surgery. The higher cost of a ci-NPT dressing might be justified with instrumented cases, as well as with certain high-risk patient populations undergoing spine surgery, given the serious consequences of an infection. Graphical Abstract: